The complete chloroplast genome and phylogenetic analysis of Manglietia ventii (Magnoliaceae) - Yuchang Wang; Dawei Wang (Mitochondrial DNA. Part B. Resources, 2022)
Manglietia ventii is a highly ornamental timber tree species that is listed as endangered on the IUCN Red List. This study was conducted on the complete chloroplast genome of M. ventii. The length of the chloroplast genome is 159,950 bp with GC content as 39.3%. One hundred and thirty-one functional genes were identified in the genome, which included 86 protein-coding genes (PCGs), 37 tRNA genes, and eight rRNA genes. The phylogenetic analysis indicated that M. ventii is most closely related to M. megaphylla and M. aromatica, and the study provides new insights into the evolution of the Magnoliaceae.